AB1264 Pilot study of the impact of a multi-biomarker disease activity test for rheumatoid arthritis (vectra™ da) on treatment decisions in community practice. (23rd January 2014) - Padula, A.S.; Nelson, B.; Sylvester, R.A.; Eisenberger, N.; Merrell, V.; Torres, A.; Cavet, G.; Li, W.; Ford, K.
Abstract : Background: Guidelines recommend routine measurement of disease activity. However, measurement does not improve outcomes unless it impacts treatment decisions. Recently, a multi-biomarker disease activity (MBDA) test for rheumatoid arthritis (RA) was validated and shown to be associated with structural damage and patient functional status. However, its impact on treatment decisions in clinical practice has not been evaluated. Objectives: The primary objective was to assess how the MBDA test affects patient treatment decisions in clinical practice. Secondary objectives included characterization of the clinical situations in which the test is used, what types of treatment changes occur, use in patient consultations and overall satisfaction with the test. Methods: Health care providers (HCPs) were recruited based on ability to accrue quickly (≥10 orders/month for 1-3 months). Only 1 HCP was included per region of the USA. HCPs were sent 2 surveys with each potentially eligible test report. One survey was completed after assessing the patient but before viewing the report. The other survey was completed after viewing the report. Eligible reports were from commercially ordered tests not yet sent to the ordering HCP and for an RA patient ≥18 years old. Exclusions included "No Result", "Exception", "Amended" or "Corrected" reports or reports for patients in clinical trials restricting the ability to make treatment changes. The percentage of treatment changes was calculated, and its 95% confidence interval was derived by the Agresti-Coull method. Results: 9 HCPs were identified and 6 agreed to participate. 108 sets of surveys were completed and 101 used in analysis. 7 were excluded for protocol exceptions. Patient characteristics for the reports included were 82% female, median age 64, median disease duration 4.5 years, median physician global 3.5, median MBDA score 44, RF status 52% positive and 18% unknown, anti-CCP status 35% positive and 24% unknown. Treatment plan changes occurred in 37.6% (38) cases, 95% CI 28.8% – 47.4%. Medications were added in 10 cases, removed in 6 and switched in 5. The dose increased in 11 cases and decreased in 1. The frequency of administration changed in 5. In 6 cases, methotrexate was changed from oral to subcutaneous. The top reasons for ordering the test were facilitating patient discussions (64.4%), routine monitoring (53.5%), assessing a patient with a comorbidity (46.5%) and confirming low disease activity (35.6%). Providers planned to use reports in 100% of patient consultations. The information provided by the test was considered very valuable for 84.2% of reports, somewhat valuable for 13.9% and not valuable for 2.0%. Conclusions: Use of the MBDA test by experienced users results in a variety of changes to treatment decisions. In this setting, the test is considered very valuable in most cases and is frequently used in patient consultations. Further studies are required to determine whether treatment changes resulting from use of the MBDA test lead to improved patient outcomes. Disclosure of Interest: A. Padula Speakers Bureau: Crescendo Bioscience, B. Nelson: None Declared, R. Sylvester Consultant for: Crescendo Bioscience, N. Eisenberger Speakers Bureau: Amgen, Abbott, Crescendo Bioscience, Janssen Biotech, Pfizer, V. Merrell: None Declared, A. Torres: None Declared, G. Cavet Employee of: Crescendo Bioscience, W. Li Employee of: Crescendo Bioscience, K. Ford Employee of: Crescendo Bioscience